Elements and compounds - Cha (New York : Crabtree Pub. Co., 1996)
An introduction to chemical elements and organic compounds.
Elements -- The periodic table -- Hydrogen -- Metals -- Metals and nonmetals -- Halogens and noble gases -- Compounds -- Chemical bonds -- Organic compounds -- Future chemistry.
"Bringing chemistry to life"--Cover.
Includes bibliographical references (p. 32) and index.
Keywords: Chemical elements -- Juvenile literature; Organic compounds -- Juvenile literature; Chemistry -- Juvenile literature; Chemical elements; Organic compounds; Chemistry